2018
DOI: 10.1007/s00540-018-2476-x
|View full text |Cite
|
Sign up to set email alerts
|

Local infiltration analgesia combined with a standardized multimodal approach including an adductor canal block in total knee arthroplasty: a prospective randomized, placebo-controlled, double-blinded clinical trial

Abstract: Performing LIA in addition to a standardized multimodal analgesia regimen results in superior pain control, demonstrated as reduced opioid needs and lower resting and dynamic pain intensity scores on the first postoperative day after TKA. Further studies are needed to establish an LIA protocol that could maximize postoperative pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
8
1
1
Order By: Relevance
“…Almost all the studies retrieved reported that LIA can provide good pain control in the first 48 h after TKA. It usually is utilized as a part of a multimodal approach for post-operative pain management [9, 30, 31]. Different compositions of LIA have been used.…”
mentioning
confidence: 99%
“…Almost all the studies retrieved reported that LIA can provide good pain control in the first 48 h after TKA. It usually is utilized as a part of a multimodal approach for post-operative pain management [9, 30, 31]. Different compositions of LIA have been used.…”
mentioning
confidence: 99%
“… 9 , 10 More recently, LIA was found to provide more efficacious pain relief compared to placebo. 7 In addition, LIA compared to standard analgesia, including femoral and sciatic nerve blocks, resulted in greater pain relief and improvement in range of motion. 11 Despite the above trend of positive results suggesting the superiority of the LIA technique, other previous reports concluded that blocking multiple nerves was preferable or at least comparable to LIA, particularly adductor canal block.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the available data and our clinical experience showed that LIA may produce a savings of up to 25% of the postoperative mean opioid consumption. 7 , 9 , 10 Based on this information, the required sample size of the study was estimated to be 47 pairs of patient (paired t -tests: effect size f = 0.36, alpha = 0.05, one-tailed power = 0.8). The sample size was increased by about 10%, resulting in 50 pairs; that is, a total of 100 patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that LIA provides a superior analgesia compared with placebo [17,18]. In addition, there might be an additive analgesic effect even when LIA was added to a standardized multimodal regimen including adductor canal block [19]. Given that multimodal analgesia has become the standard of care for patients undergoing joint arthroplasty [20], use of LIA is expected to increase in these patients.…”
Section: Discussionmentioning
confidence: 99%